Download presentation
Presentation is loading. Please wait.
Published byAshlynn Powers Modified over 9 years ago
1
Top 10 of Set 1 Review Domain and Range Inverses Odd and even rules for a function Questions: 2,3,7,10,11,12,13,20,23,31
2
Generally, the domain is implied to be the set of all real numbers that yield a real number functional value (in the range). Some restrictions to domain: 1. Denominator cannot equal zero (0). 2. Radicand must be greater than or equal to zero (0). 3. Practical problems may limit domain. Domain of a Function
3
What’s the range of the following a)y=2x+5 b) f(x)=4-x 2 Range of a function
4
Horizontal line test Horizontal line test. passes inverse is a function If the original function passes the horizontal line test, then its inverse is a function. does not pass inverse is not a function If the original function does not pass the horizontal line test, then its inverse is not a function. Does the Function have an Inverse? Graph does not pass the horizontal line test, therefore the inverse is not a function.
5
Find an inverse of y = -3x+6. Steps: -switch x & y -solve for y y = -3x+6 x = -3y+6 x-6 = -3y
6
Meaning find f(g(x)) and g(f(x)). If they both equal x, then they are inverses. Verify that f(x)=-3x+6 and g(x)= -1 / 3 x+2 are inverses Verify the functions are inverses
7
FUNCTIONSFUNCTIONS Symmetric about the y axis Symmetric about the origin
8
1. A function given by y = f(x) is even if, for each x in the domain, f(-x) = f(x). 2. A function given by y = f(x) is odd if, for each x in the domain, f(-x) = - f(x). Even and Odd Functions
9
Important parts of Trig Graph Determine the amplitude, period, and phase shift of y = 2sin(3x- ) Solution: Amplitude = |A| = 2 period = 2 /K = 2 /3 phase shift = -C/K = /3 to the right
10
Sum and Difference Identities for the Cos Function Trig Identities cos ( + ) = cos cos – sin sin cos ( – ) = cos cos + sin sin Sum and Difference Identities for the Sin Function sin ( + ) = sin cos + cos sin sin ( – ) = sin cos – cos sin Sum and Difference Identities for the Tan function tan ( + ) = tan + tan 1 - tan tan tan ( – ) = tan – tan 1 + tan tan
Similar presentations
© 2025 SlidePlayer.com. Inc.
All rights reserved.